PETROGENESIS OF SILICATE INCLUSIONS IN THE WEEKEROO STATION IIE IRON METEORITE: DIFFERENTIATION, REMELTING, AND DYNAMIC MIXING - PART II: CHEMICAL COMPOSITION OF AGGLUTINATE GLASS AS A TEST OF THE undefinedFUSION OF THE FINEST FRACTIONundefined (F3) MODEL - Ruzicka A.; Fowler G.W.; Snyder G.A.; Prinz M.; Papike J.J.; Taylor L.A. (My University, 1999)
The Weekeroo Station IIE iron meteorite contains a variety of felsic and mafic inclusions enclosed in an FeNi-metal host. Petrographic, EMP, and SIMS data suggest that the petrogenesis of the silicates was complex, and included differentiation, remelting, FeO-reduction, and dynamic mixing of phases.Differentiation produced a variety of olivine-free inclusion assemblages, ranging from pyroxene + plagioclase + tridymite with peritectic compositions, to coarse orthopyroxene, to plagioclase + tridymite and its glassy equivalent. Individual phases have similar trace-element abundances and patterns, despite large variations in inclusion textures, modes, and bulk compositions, probably as a result of mechanical separation of pre-existing phases in an impact event that dynamically mixed silicates with the metallic host. Trace-element data imply that augite and plagioclase grains in different inclusions crystallized from the same precursor melt, characterized by relatively unfractionated REE abundances of ~20-30 x CI-chondrites except for a negative Eu anomaly. Such a precursor melt could have been produced by ~2-5% equilibrium partial melting of an H-chondrite silicate protolith, or by higher degrees of partial melting involving subsequent fractional crystallization. Glass appears to have formed by the remelting of pre-existing plagioclase and orthopyroxene, in a process that involved either disequilibrium or substantial melting of these phases. During remelting, silicate melt reacted with the FeNi-metal host, and FeO was reduced to Fe-metal. Following remelting and metal-silicate mixing, inclusions apparently cooled at different rates in a near-surface setting on the parent body; glass- or pigeonite-bearing inclusions cooled more rapidly (=<2.5°C/hr between 1000-850°C) than pigeonite-free, largely crystalline inclusions.The results of this study point to two likely models for forming IIE iron meteorites, both involving collision between an FeNi-metal impactor and either a differentiated or undifferentiated silicate-rich target of H-chondrite affinity. Each model has difficulties and it is possible that both are required to explain the diverse IIE group.